Health Related Quality of Life among Stroke Patients in Bangladesh - Binay Bhushan Mozumder; Sreekanto Kumar; Mahbub Alam; Dr. Fardina Rahman Omi; Halima Akter (International Journal of Medical Science and Clinical Research Studies, 2025)
Background: Stroke is a leading cause of disability and mortality worldwide, with significant impacts on patients' physical, psychological, and social well-being. In Bangladesh, the burden of stroke is increasing due to aging populations, lifestyle changes, and limited access to quality healthcare. Objective: This study aims to determine factors that may impact quality of life following a stroke and to evaluate overall and domain-specific QoL in post-stroke patients using the SS-QoL scale. Methods: The study was a cross-sectional study which was conducted over one year duration. Based on inclusion and exclusion criteria 125 samples were recruited from Neurology and Neurosurgery department of Dhaka Medical College Hospital. A face-to-face interview carried out. Overall domain specific score was expressed in mean and percentages. Result: Health related quality of life scale was physical & energy of the participants mean 1.08, (SD ±. 31), family & social mean 1.36, (SD ±.73), Mood & personality mean 1.45 (SD ±. 87). The study concluded that health related quality of life scale influence better outcomes of the stroke participants. Conclusion: Study revealed that health related quality of life among stroke patients had minimum HRQoL domain scores.